Building a theoretical basis and public support for nutrition sensitive value chains - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
In Phase I, A4NH researchers with partners developed a framework for considering how and whether to invest in nutrition-sensitive value chains. Since then, the framework has been endorsed by the Global Forum on Food Security and Nutrition and adapted and applied by several Rome-based agencies. This updated outcome story describes how the framework has been adapted into practical guidance, published by the International Fund for Agricultural Development (IFAD), for those interested in designing nutrition-sensitive value chain projects.